2020
DOI: 10.1038/s41598-020-79207-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine allergy and an attempt at desensitization therapy in patients with inflammatory bowel disease

Abstract: Mesalazine is a key drug used for remission induction and maintenance therapy in inflammatory bowel disease (IBD). We sometimes encounter patients who develop allergic reactions to the drug and inevitably discontinue treatment. Of 692 patients who received mesalazine for IBD between 2014 and March 2020, 33 diagnosed with mesalazine allergy (43 episodes) were included, and their clinical manifestations were evaluated. For ten patients undergoing desensitization therapy, therapeutic outcomes were evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
6
15
1
Order By: Relevance
“…Although the number of cases was limited, the success rate was not affected by the results of DLST or desensitization therapy. A recent report also showed that the success rate of the desensitization treatment was not related to the results of DLST, which was similar to the course of this study.‍ ( 36 )…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the number of cases was limited, the success rate was not affected by the results of DLST or desensitization therapy. A recent report also showed that the success rate of the desensitization treatment was not related to the results of DLST, which was similar to the course of this study.‍ ( 36 )…”
Section: Discussionsupporting
confidence: 90%
“…Hepatotoxicity,‍ ( 26 , 27 ) pancreatitis,‍ ( 28 , 29 ) interstitial nephritis,‍ ( 30 , 31 ) pneumonia,‍ ( 32 ) and pericarditis‍ ( 12 , 33 ) have been reported as rare but serious symptoms of mesalamine intolerance. The frequency of these side effects does not increase with increasing mesalamine dose,‍ ( 34 ) but these symptoms are always dose-dependent and have been reported to resolve with decreasing dose.‍ ( 35 ) The frequency of fever (85.7%), a typical symptom of 5-ASA intolerance, observed in this study was comparable to that reported in recent years (93.0%).‍ ( 36 ) In addition, the clinical course of the cases in this study was similar to previous reports in that symptoms appeared within 2 weeks and serum CRP levels were high.‍ ( 25 , 36 )…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several reports have pointed to varied adverse drug reactions associated with 5-ASA-containing compounds, the most frequent being fever and gastrointestinal reactions with an incidence of approximately 5%. The mechanism behind these is thought to be a drug-induced hypersensitivity syndrome, with desensitisation therapy successful in up to 90% of cases, according to a recent study 1. Much rarer adverse effects include pericarditis, eosinophilic pneumonia, pancreatitis, interstitial nephritis and hepatotoxicity 2–4.…”
Section: Case Presentationmentioning
confidence: 99%
“…5-ASA, also termed mesalazine, is often associated with fever, diarrhea, abdominalgia, and hematochezia ( Matsumoto and Mashima, 2020 ). However, cardiotoxicity has been reported as a rare but potentially fatal adverse reaction ( Kristensen et al, 1990 ).…”
Section: Introductionmentioning
confidence: 99%